Enhancing dissolution profile of diazepam using hydrophilic polymers by solid dispersion technique - Howlader, Md. Sariful Islam; Chakrabarty, Jayanta Kishor; Faisal, Khandokar Sadique; Kumar, Uttom; Sarkar, Md. Raihan; Khan, Mohammad Firuz (International Current Pharmaceutical Journal, 2012)
The aim of the present study was to improve the solubility and dissolution rate of a poorly water-soluble drug by a solid dispersion technique, in order to investigate the effect of these polymers on release mechanism from solid dispersions. Diazepam was used as a model drug to evaluate its release characteristics from different matrices. Solid dispersions were prepared by using polyethylene glycol 6000 (PEG-6000), HPMC, HPC and Poloxamer in different drug-to-carrier ratios (1:2, 1:4, 1:6, 1:8, 1:10). The solid dispersions were prepared by solvent method. The pure drug and solid dispersions were characterized by in vitro dissolution study. Distilled water was used as dissolution media, 1000 ml of distilled water was used as dissolution medium in each dissolution basket at a temperature of 37°C and a paddle speed of 100 rpm. The very slow dissolution rate was observed for pure Diazepam and the dispersion of the drug in the polymers considerably enhanced the dissolution rate. This can be attributed to improved wettability and dispersibility, as well as decrease of the crystalline and increase of the amorphous fraction of the drug. SEM (Scanning Electron microscope) studies shows that the solid dispersion having a uniform dispersion. Solid dispersions prepared with PEG-6000, Poloxamer showed the highest improvement in wettability and dissolution rate of Diazepam. Solid dispersion containing polymer prepared with solvent method showed significant improvement in the release profile as compared to pure drug, Diazepam. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12453 International Current Pharmaceutical Journal 2012, 1(12): 423-430